Alteration of ACTH and Cortisol Levels After Estradiol Valerate Treatment in a Male Subject With Gender Dysphoria: A Case Report - Anno, Takatoshi; Kawasaki, Fumiko; Shigemoto, Ryo; Irie, Shintaro; Mune, Tomoatsu; Kaku, Kohei; Kaneto, Hideaki (Frontiers in Endocrinology, 2019)
Background: The number of subjects with gender dysphoria has been increasing. In general, male-to-female transsexual subjects are treated with estradiol valerate therapy. In this report, we showed the time course of ACTH and cortisol levels after estradiol valerate injection in a male subject with gender dysphoria. It seemed that alteration of estradiol level influenced ACTH and cortisol levels via some pathway. Case presentation: A 31-year-old man with estradiol valerate therapy for gender dysphoria was referred due to the elevation of serum cortisol levels. She started hormone therapy at 26 years old. Her laboratory analyses showed an elevation of plasma ACTH and cortisol levels. There were no remarkable changes in adrenal gland and pituitary gland. Her estradiol levels were elevated 7 days after estradiol valerate injection but they were not detected 18 days after such treatment. Interestingly, plasma ACTH and serum cortisol levels were moderately decreased 7 days after estradiol valerate injection, but both of them were markedly elevated 18 days after such treatment. Conclusions: We should bear in mind the possibility of elevation in plasma ACTH and serum cortisol levels when we start estradiol valerate injection in subjects with gender dysphoria. In addition, we may need to check ACTH and cortisol levels when we use estrogen replacement therapy for a long period of time in subjects with gender dysphoria.